Genomic analysis of host-pathogen interaction between Fusarium graminearum and wheat during early stages of disease development - Goswami, R.S.; Xu, J.R.; Trail, F.; Hilburn, K.; Corby Kistler H.
Fusarium graminearum strains responsible for causing the plant disease Fusarium head blight vary greatly in their ability to cause disease and produce mycotoxins on wheat. With the goal of understanding fungal gene expression related to pathogenicity, three cDNA libraries were created by suppression subtractive hybridization using wheat heads inoculated with a highly aggressive strain and either water or a less aggressive strain of this pathogen. Eighty-four fungal genes expressed during initial disease development were identified. The probable functions of 49 of these genes could be inferred by bioinformatic analysis. Thirty-five ESTs had no known homologues in current databases and were not identified by ab initio gene prediction methods. These ESTs from infected wheat heads probably represent F. graminearum genes that previously were not annotated. Four genes represented in one of these libraries were selected for targeted gene replacement, leading to the characterization of a two-component response regulator homologue involved in pathogenicity of the fungus. The mutants for this gene showed reduced sporulation and delayed spread of Fusarium head blight on wheat.